Teaching Model Development of English Listening Skills by Using Lingoclip to Increase Students’ Listening Skills at SMP Swasta Pelita Kasih School Tanjung Morawa - Ronika Wina Pakpahan; Arsen Pasaribu; Sahlan Tampubolon; Erika Sinambela (Didaktika: Jurnal Kependidikan, 2023)
This research shows that there are several problems experienced by junior high school students in learning listening skills. This research aims to find out the development of listening teaching model using lingoclip in increasing listening skill.The researcher tried to reveal the problems that occur in the ability of junior high school students.Type of research was a class action research descriptive quantitative. Based on the results of the pre-test, the pre-test mean score was 56,94 and the mean score in the post-test was 80,47. It can be seen that the students' skill in listening by using AIR Learning model was increased. From these calculations, it can be inferred that there was a difference of students' scores before and after receiving the treatment. The development from the research is when using the AIR Learning model, the results obtained increased by approx. 48%. Based on the data analysis, the researcher found that AIR Learning can improve students’ skill in listening. As the result from the pre-test and post-test mean scores which were given. The improvement of mean score was 56,94 to 80,47. It means that there was a significant difference of achievement between the students who were taught by AIR Learning model and the students who were taught without AIR Learning model.The data also showed that students felt that AIR Learning model could help them in listening. Most of them also responded that they attempt to use AIR Learning model in their daily listening.